Digital image processing. - Seeram E (Radiologic Technology)
Digital image processing is now commonplace in radiology, nuclear medicine and sonography. This article outlines underlying principles and concepts of digital image processing. After completing this article, readers should be able to: List the limitations of film-based imaging. Identify major components of a digital imaging system. Describe the history and application areas of digital image processing. Discuss image representation and the fundamentals of digital image processing. Outline digital image processing techniques and processing operations used in selected imaging modalities. Explain the basic concepts and visualization tools used in 3-D and virtual reality imaging. Recognize medical imaging informatics as a new area of specialization for radiologic technologists.